Evaluation of thermal and mechanical properties of demonstration wall utilizing phase change cementitious materials - Jan Červenka; Michaela Herzfeldt; Antonio Caggiano; Eduardus Koenders (Acta Polytechnica CTU Proceedings, 2022)
International project PoroPCM involves partners from Germany, Czech Republic, Spain and Japan with the objective to develop new multifunctional Phase Change Materials modified porous cementitious nanocomposite (PoroPCM). Such material can be utilized for storing heat energy in the insulation layer of buildings compared to commonly used insulation materials since the phase change increases heat capacity. This enhanced feature reduces the amount of energy necessary for running the heating/cooling system. For the testing of the newly developed phase change cementitious composite a demonstration wall will be developed and tested for its thermal as well as mechanical performance. The topic of the paper is the description of the properties of the new phase change cementitious nanocomposite. The main emphasis of the paper is the description of the demonstration wall behaviour under typical environmental conditions. The wall design is supported by numerical simulation of the wall physical parameters. The numerical modelling involves the definition of suitable numerical models for the simulation of the thermal properties of the new phase change nanocomposite. The numerical model is then used to demonstrate the performance of the wall layer design. The presented pilot results show efficiency increase of the insulation material in the range 15-70 %. Also modelling of wind resistance of the layered structure is included. The developed wall design and PoroPCM material will be tested and verified by a large scale test in the final year of the project.